Laminate and its manufacturing method, packaging body and packaged article

The laminate structure, featuring a polyamide intermediate substrate layer and specific adhesive and sealant layers, addresses the challenges of adsorption resistance and laminate strength in packaging materials, particularly when exposed to highly permeable substances.

JP7666221B2Active Publication Date: 2025-04-22TOPPAN HOLDINGS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021132273
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-16
Publication Date
2025-04-22
Estimated Expiration
2041-08-16

AI Technical Summary

Technical Problem

Laminates used for packaging, especially those with an intermediate substrate layer, face challenges in maintaining adsorption resistance and laminate strength due to highly permeable substances, which can lead to delamination.

Method used

A laminate structure is proposed, including a substrate layer, a barrier layer, an intermediate substrate layer with a polyamide resin, a first adhesive layer with an isocyanate compound, an adhesive resin layer made of low density polyethylene or ethylene-methacrylic acid copolymer, and a sealant layer with a cyclic olefin resin, which enhances adsorption resistance and prevents laminate strength deterioration.

Benefits of technology

The proposed laminate structure effectively maintains adsorption resistance and prevents the deterioration of laminate strength due to highly permeable substances, ensuring the integrity and functionality of the packaging material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666221000003
    Figure 0007666221000003
  • Figure 0007666221000004
    Figure 0007666221000004
  • Figure 0007666221000005
    Figure 0007666221000005
Patent Text Reader

Abstract

To provide a laminate excellent in absorption resistance to a component contained in a content, and suppressed in reduction of laminate strength by a strongly permeable substance in a laminate including an intermediate substrate layer between a barrier layer and a sealant layer.SOLUTION: The laminate according to an embodiment of the present invention includes a substrate layer, a barrier layer, an intermediate substrate layer, a first adhesion layer, an adhesive resin layer, and a sealant layer in this order. The intermediate substrate layer contains a polyamide resin, the first adhesion layer contains an isocyanate compound having two or more isocyanate groups, the adhesive resin layer contains a low density polyethylene resin or an ethylene-methacrylic acid copolymer, and the sealant layer contains a cyclic olefin-based resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a method for producing the same, a package, and a packaged article. [Background technology]

[0002] In laminates used as packaging materials, etc., thermoplastic resins are used in the sealant layers, and as such thermoplastic resins, polyethylene resins, polypropylene resins, etc. are particularly used because of their excellent lamination processability and heat sealability.

[0003] However, while these resins can achieve high adhesive strength due to their excellent heat sealability, they tend to adsorb ingredients contained in medicines, foods, etc. Therefore, packages that include a sealant layer made of such a resin in contact with the space that contains the contents tend to cause the contents to change or deteriorate.

[0004] For this reason, polyester resins and polyacrylonitrile resins, which are low-adsorption materials, have been used in the sealant layers of laminates used in packaging medicines, foods, etc. However, polyester resin films have problems with poor heat sealability, and polyacrylonitrile resin films have poor film-forming properties and also have problems from the standpoints of cost and stable procurement.

[0005] Patent Document 1 discloses a biaxially oriented film made of a cyclic olefin resin, with the objective of providing a packaging film that has low adsorption and excellent toughness and is suitable for packaging medicines, foods, etc. In this document, this cyclic olefin resin film is used as a sealant layer in a laminate consisting of polyethylene terephthalate / barrier layer (aluminum foil) / sealant layer, and the aluminum foil and the sealant layer are bonded together by a dry lamination method (paragraph 0043).

[0006] In this way, when bonding a low-adhesive sealant layer and a barrier layer such as aluminum foil, a dry lamination method is generally used, and a two-part curing urethane adhesive is usually used as the dry lamination adhesive.

[0007] However, when the contents to be packaged in the packaging material contain strongly penetrating substances such as fragrances for bath agents, poultice ingredients, alcohol, or various disinfectants, there is a problem that the strongly penetrating substances permeate into the laminate, which is the packaging material, during long-term storage. Since the barrier layer has gas barrier properties, the strongly penetrating substances that permeate the laminate are trapped between the barrier layer and the sealant layer, dissolving the adhesive layer between the barrier layer and the sealant layer, causing a decrease in laminate strength. In particular, when a two-component curing urethane adhesive is used, the strongly penetrating substances significantly reduce the laminate strength between the barrier layer and the sealant layer, resulting in a problem of delamination (peeling). For this reason, when a low-adsorption sheet such as that in Patent Document 1 is used as the sealant layer of a packaging laminate, it is desirable to improve resistance to strongly penetrating substances in addition to adsorption resistance.

[0008] Patent Document 2 discloses a one-component curing adhesive containing an isocyanate compound as an adhesive for suppressing a decrease in laminate strength caused by trapping of highly penetrative substances between a barrier layer and a sealant layer in a laminate consisting of a barrier layer (aluminum foil or the like) / adhesive layer / sealant layer. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2017 / 033810 [Patent Document 2] Patent No. 4306278 Summary of the Invention [Problem to be solved by the invention]

[0010] The adhesive containing an isocyanate compound disclosed in Patent Document 2 is an adhesive developed to suppress a decrease in laminate strength between a barrier layer and a sealant layer due to the strong permeability of a strongly penetrating substance in a laminate consisting of a barrier layer / adhesive layer / sealant layer. As a result of intensive research by the present inventors, it was found that in a laminate including an intermediate substrate layer between a barrier layer and a sealant layer, even if the above adhesive is used as an adhesive layer, there are cases where it is not possible to suppress a decrease in laminate strength due to a strongly penetrating substance.

[0011] The present invention aims to provide a laminate used as a packaging material, which includes an intermediate substrate layer between a barrier layer and a sealant layer, which has excellent adsorption resistance to components contained in the contents and which inhibits a decrease in laminate strength due to highly penetrative substances. [Means for solving the problem]

[0012] According to a first aspect of the present invention, there is provided a laminate comprising, in this order, a substrate layer, a barrier layer, an intermediate substrate layer, a first adhesive layer, an adhesive resin layer, and a sealant layer, wherein the intermediate substrate layer contains a polyamide-based resin, the first adhesive layer contains an isocyanate compound having two or more isocyanate groups, the adhesive resin layer contains a low-density polyethylene resin or an ethylene-methacrylic acid copolymer, and the sealant layer contains a cyclic olefin-based resin.

[0013] According to a second aspect of the present invention, there is provided a method for producing a laminate related to the first aspect, comprising forming a first laminate having the base material layer, the barrier layer, the intermediate base material layer, and the first adhesive layer in this order, forming the adhesive resin layer by an extrusion lamination method, and laminating the first laminate and the sealant layer with the adhesive resin layer sandwiched between them so that the first adhesive layer and the sealant layer face each other.

[0014] According to a third aspect of the present invention, there is provided a package including the laminate according to the first aspect.

[0015] According to a fourth aspect of the present invention, there is provided a packaged article including the package according to the third aspect and contents packaged therein. Effect of the Invention

[0016] According to the present invention, there is provided a laminate used as a packaging material, which includes an intermediate substrate layer between a barrier layer and a sealant layer, which has excellent adsorption resistance to components contained in the contents and which inhibits a decrease in laminate strength due to highly penetrative substances. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a partial cross-sectional view illustrating an example of a laminate according to an embodiment of the present invention. [Diagram 2] FIG. 13 is a partial cross-sectional view illustrating a laminate according to a modified example. [Diagram 3] FIG. 11 is a partial cross-sectional view illustrating a laminate according to another modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The embodiment described below is a more specific embodiment of any of the above aspects. Elements having the same or similar functions are given the same reference numerals, and duplicated descriptions will be omitted.

[0019] FIG. 1 is a cross-sectional view that illustrates an example of a laminate according to an embodiment of the present invention. 1 includes, in this order, a base material layer 11, a barrier layer 14, an intermediate base material layer 17, a first adhesive layer 18, an adhesive resin layer 19, and a sealant layer 20. The first adhesive layer 18 and the adhesive resin layer 19 are interposed between the intermediate base material layer 17 and the sealant layer 20, and bond the intermediate base material layer 17 and the sealant layer 20 together. According to this embodiment, even in a configuration in which the intermediate base material layer 17 is included between the barrier layer 14 and the sealant layer 20, a decrease in laminate strength caused by a highly penetrative substance between the barrier layer 14 and the sealant layer 20 can be suppressed. Each layer contained in the laminate 1 will be described below.

[0020] (base material layer) The base layer 11 is, for example, paper, a resin film, or a combination thereof. As the resin film, for example, a polypropylene film, a polyester film, a nylon film, or cellophane can be used.

[0021] The resin film may be a stretched film from the viewpoint of imparting mechanical strength to the laminate 1. Inclusion of a uniaxially or biaxially stretched polyethylene terephthalate film (PET) as the base layer 11 is advantageous in obtaining a laminate 1 with high stiffness.

[0022] The thickness of the base layer 11 is, according to one example, in the range of 3 μm to 200 μm, and according to another example, in the range of 6 μm to 30 μm.

[0023] Depending on the application, a printed layer may be provided on the main surface of the base layer 11. The printed layer may be provided on the main surface on the barrier layer 14 side, or on the back surface, or on both of them.

[0024] (Barrier layer) The barrier layer 14 is a layer having gas barrier properties that reduce the permeability of gases such as water vapor and oxygen.

[0025] The barrier layer 14 may be, for example, a single layer made of an aluminum layer or an inorganic oxide layer, or may be a multilayer structure including an aluminum layer or an inorganic oxide layer. The barrier layer 14 is, for example, an aluminum foil, an aluminum vapor deposition film, or a transparent vapor deposition film. Note that a polyethylene terephthalate (PET) resin layer constitutes the barrier layer 14 in combination with an aluminum layer or an inorganic oxide layer, and layers consisting of only this resin layer are excluded from the barrier layer 14.

[0026] The thickness of the aluminum foil is preferably in the range of 3 μm to 200 μm, and more preferably in the range of 5 μm to 100 μm. If the aluminum foil is too thin, it is difficult to handle when it is bonded to the substrate. On the other hand, if the aluminum foil is thicker than a certain thickness, the barrier property is not improved, the cost is high, and the flexibility of the packaging material tends to be poor, making it difficult to handle.

[0027] The aluminum vapor-deposited film is a film in which an aluminum layer is vapor-deposited on a first resin layer, which is, for example, a biaxially oriented polyethylene terephthalate film, a biaxially oriented nylon film, or a biaxially oriented polypropylene film.

[0028] The thickness of the first resin layer is not particularly limited, but in one example, it is in the range of 3 μm to 200 μm, and in another example, it is in the range of 6 μm to 30 μm. In one example, the thickness of the aluminum deposition layer is in the range of 5 nm to 100 nm. If the aluminum deposition layer is too thin, it may not be possible to sufficiently prevent the intrusion of gases such as water vapor and oxygen. On the other hand, a thick aluminum deposition layer not only increases the cost, but also makes the deposition layer more susceptible to cracking, which may lead to a decrease in barrier properties.

[0029] The transparent deposition film is formed by forming an inorganic oxide layer on the second resin layer by means of a vacuum deposition method, a sputtering method, etc. The second resin layer can be the same film as the first resin layer described above.

[0030] The inorganic oxide layer is made of an inorganic oxide such as silicon oxide, aluminum oxide, magnesium oxide, etc. Most inorganic oxide thin film layers are colorless or very lightly colored transparent layers, and can be suitably used when transparency is required as a packaging material. In addition, unlike metal layers, they are permeable to microwaves, so they can also be used as packaging materials for foods to be heated in a microwave oven.

[0031] The thickness of the inorganic oxide layer is, for example, in the range of 5 nm to 300 nm, and in another example, in the range of 10 nm to 150 nm. If the inorganic oxide layer is too thin, a uniform film may not be obtained or the thickness may be insufficient, and the inorganic oxide layer may not fully function as the barrier layer 14. On the other hand, if the inorganic oxide layer is too thick, cracks may occur in the inorganic oxide layer when the laminate 1 is bent or pulled.

[0032] As the transparent deposition film, for example, commercially available products such as "GL FILM" and "PRIME BARRIER (registered trademark)" (both manufactured by Toppan Printing Co., Ltd.) can be used.

[0033] When the barrier layer 14 is a single layer made of, for example, a vapor deposition layer, it can be laminated on one main surface of the substrate 11 as shown in Fig. 1. When the barrier layer 14 is, for example, an aluminum foil, an aluminum vapor deposition film, or a transparent vapor deposition film, it can be dry laminated on one main surface of the substrate layer 11 via an adhesive layer (not shown). As the adhesive layer, a two-component curing urethane adhesive that is generally used as an adhesive for dry lamination can be used, and a known coating method such as a gravure coating method or a roll coating method can be used.

[0034] (Intermediate substrate layer) The intermediate substrate layer 17 contains a polyamide resin. The intermediate substrate layer 17 improves the strength of the laminate 1. Furthermore, since the intermediate substrate layer 17 contains a polyamide resin, the adhesive strength with the adjacent first adhesive layer 18 is increased, which contributes to suppressing delamination (peeling) caused by a highly penetrative substance. That is, the amide bond contained in this polyamide resin reacts with the isocyanate bond of the isocyanate compound contained in the adjacent first adhesive layer 18 to form a strong urea bond at the interface. As a result, the decrease in laminate strength caused by the highly penetrative substance is suppressed, and the occurrence of lamination (peeling) is prevented.

[0035] The polyamide resin is, for example, a polyamide containing an aliphatic skeleton. For example, an aliphatic polyamide polymer or an aliphatic polyamide copolymer is used as the polyamide resin. Specific examples of the polyamide resin include aliphatic polyamide polymers such as nylon 6, nylon 66, nylon 610, nylon 612, nylon 11, nylon 12, and nylon 46, and aliphatic polyamide copolymers such as nylon 6-66, nylon 6-610, nylon 66-610, and nylon 6-12. The aliphatic polyamides can be used alone or as a mixture of two or more kinds.

[0036] The intermediate base layer 17 may further include a material other than the polyamide-based resin. For example, the intermediate base layer 17 may further include an additive such as a slip agent. The proportion of the polyamide-based resin in the mass of the intermediate base layer 17 is preferably 99.0 mass% or more, and more preferably 99.9 mass% or more.

[0037] The thickness of the intermediate substrate layer 17 is preferably in the range of 3 μm to 200 μm, and more preferably in the range of 6 μm to 30 μm.

[0038] The intermediate base material layer 17 may be dry laminated, for example, via an adhesive layer (not shown) onto the main surface of the barrier layer 14 opposite to the base material layer 11. As the adhesive layer, a two-component curing urethane adhesive that is generally used as an adhesive for dry lamination can be used, and a known coating method such as a gravure coating method or a roll coating method can be used.

[0039] Depending on the application, a printed layer may be provided on the main surface of the intermediate base material layer 17. The printed layer may be provided on the main surface on the base material layer 11 side of the two main surfaces of the intermediate base material layer 17, or on the back surface thereof, or on both of them.

[0040] (1st adhesive layer) The first adhesive layer 18 is a layer derived from a one-component curing adhesive containing an isocyanate compound having two or more isocyanate groups, and contains an isocyanate compound having two or more isocyanate groups.

[0041] Examples of isocyanate compounds having two or more isocyanate groups include diisocyanate monomers, or adduct type, biuret type, or trimer (isocyanurate) type derivatives of diisocyanate monomers. Specific examples of isocyanate compounds having two or more isocyanate groups include various diisocyanate monomers such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and hydrogenated products thereof. In addition, trifunctional derivatives such as adduct types obtained by reacting these diisocyanate monomers with trifunctional active hydrogen-containing compounds such as trimethylolpropane and glycerol, biuret types obtained by reacting these diisocyanate monomers with water, and trimer (isocyanurate) types utilizing self-polymerization of isocyanate groups, and multifunctional derivatives having more than one functional group can be used.

[0042] The first adhesive layer 18 forms a two-layer structure with the adjacent adhesive resin layer 19, and bonds the intermediate base material layer 17 and the sealant layer 20. The cooperation of these two layers improves the laminate strength between the barrier layer 14 and the sealant layer 20, and even if various highly permeable substances, including volatile substances such as alcohol, medicinal ingredients, and fragrance ingredients, act on the laminate 1, the laminate strength between the barrier layer 14 and the sealant layer 20 is not reduced, providing the desired adhesion and resistance to highly permeable contents.

[0043] The first adhesive layer 18 can be formed, for example, by applying a coating liquid containing the above-mentioned diisocyanate monomer or a derivative thereof in a solid content ratio of, for example, 1.0 to 10.0 mass % to the main surface of the intermediate substrate layer 17 opposite to the substrate layer 11. The mass per area of ​​the first adhesive layer 18 (in a dry state) is 0.05 to 0.25 g / m2 and preferably in the range of 0.10 to 0.20 g / m 2 It is more preferable that the range is .

[0044] (adhesive resin layer) The adhesive resin layer 19 contains a low-density polyethylene resin (LDPE) or an ethylene-methacrylic acid copolymer (EMAA). The adhesive resin layer 19 exhibits good adhesive strength to the sealant layer 20, and therefore, in cooperation with the first adhesive layer 18 exhibiting good adhesive strength to the intermediate substrate layer 17 containing a polyamide resin, improves the lamination strength between the barrier layer 14 and the sealant layer 20, thereby providing the laminate 1 with the desired adhesiveness and strong permeation resistance to contents.

[0045] The adhesive resin layer 19 is an extrusion resin layer formed by extrusion lamination. That is, the adhesive resin layer 19 is formed by extrusion lamination of a molten resin containing low-density polyethylene resin (LDPE) or ethylene-methacrylic acid copolymer (EMAA) on the main surface of the intermediate base material layer 17 on which the first adhesive layer 18 is formed, or on one of the main surfaces of the sealant layer 20.

[0046] Low-density polyethylene resin (LDPE) is obtained by a known manufacturing method such as a high-pressure method. Low-density polyethylene resin is obtained, for example, by polymerizing ethylene obtained by pyrolysis of naphtha. In one example, the low-density polyethylene resin has a melt flow rate (MFR) in the range of 3.6 g / 10 min to 13.0 g / 10 min when the temperature is 190° C. and the load is 21.168 N (=2.16 kgf) and is preferably in the range of 4.0 g / 10 min to 13.0 g / 10 min, more preferably in the range of 5 g / 10 min to 10.5 g / 10 min. The melt flow rate (MFR) described here is a measured value obtained by a method conforming to JIS K7210:1999. Specifically, the melt flow rate (MFR) is a measured value of the weight of resin discharged in 10 minutes when a load of 2.16 kgf is applied to the resin at 190° C. Hereinafter, the term "melt flow rate (MFR)" will mean the value obtained by this method.

[0047] When a low density polyethylene resin (LDPE) having a melt flow rate (MFR) in the above range is used, physical properties suitable for extrusion lamination are obtained, and even when high speed film production is performed, problems are unlikely to occur. In this case, a homogeneous layer can be formed.

[0048] The density of low-density polyethylene resin (LDPE) is 0.915 g / cm 3 ~0.925g / cm 3 and preferably in the range of 0.915 g / cm 3 ~0.922g / cm 3 It is more preferable that the density is in the range of 100 to 2000. If the density of the low-density polyethylene resin is too low, the film formation of the adhesive resin layer 19 is likely to be unstable. If the density of the low-density polyethylene resin is too high, the film formation is unstable. The density described here is a measured value obtained by a method in accordance with JIS K7112:1999.

[0049] Commercially available low-density polyethylene resins (LDPE) include, for example, "LC607K" (temperature 190°C, MFR at load 21.168N: 8.0g / 10min, density: 0.919g / cm 3 ) and "LC520" (MFR at 190°C and load of 21.168N: 3.6g / 10min, density: 0.923g / cm 3 These resins are all manufactured by Japan Polyethylene Corporation. In addition, LDPE “L417” manufactured by Sumitomo Chemical Co., Ltd. can also be suitably used as the adhesive resin layer 19.

[0050] The low-density polyethylene resin (LDPE) contained in the adhesive resin layer 19 has a different number of carbon atoms in the side chain branches relative to the main chain from the linear low-density polyethylene resin. The low-density polyethylene resin has long-chain branches with more than about 20 carbon atoms. On the other hand, the linear low-density polyethylene resin does not have long-chain branches with more than about 20 carbon atoms. The low-density polyethylene resin is superior to the linear low-density polyethylene resin in that it is less likely to cause the edge vibration phenomenon or neck-in phenomenon during extrusion film formation. The low-density polyethylene resin is also superior to the linear low-density polyethylene resin in terms of tearability.

[0051] When the adhesive resin layer 19 and the sealant layer 20 are laminated using an extrusion lamination method, a good film can be formed if the melting point of the low-density polyethylene resin is in the range of 100° C. to 120° C. It is more preferable that the melting point of the low-density polyethylene resin (LDPE) is in the range of 100° C. to 110° C. If the melting point is 120° C. or higher, processing becomes difficult due to the edge vibration phenomenon and the neck-in phenomenon.

[0052] The methacrylic acid content (hereinafter referred to as the acid content) of the ethylene-methacrylic acid copolymer (EMAA) is preferably in the range of 4% by mass to 11% by mass. If the acid content is excessively small, the adhesive strength between the adhesive resin layer 19 and the first adhesive layer 18 tends to decrease, increasing the possibility of problems such as delamination occurring during long-term storage. Also, if the acid content is excessively high, the adhesive strength between the adhesive resin layer 19 and the sealant layer 20 tends to decrease.

[0053] The ethylene-methacrylic acid copolymer (EMAA) preferably has an MFR in the range of 7.0 g / 10 min to 15.0 g / 10 min.

[0054] When an ethylene-methacrylic acid copolymer (EMAA) having a melt flow rate within the above range is used, physical properties suitable for extrusion lamination are obtained, and even when high-speed film production is performed, problems are unlikely to occur. In this case, a homogeneous layer can be formed.

[0055] The melting point of the ethylene-methacrylic acid copolymer (EMAA) is preferably in the range of 90°C to 110°C. The optimum extrusion temperature of a suitable cyclic olefin resin is relatively low. When an ethylene-methacrylic acid copolymer having a low melting point is used, the difference between the melting point of the ethylene-methacrylic acid copolymer and the glass transition temperature of the cyclic olefin resin becomes small. That is, the optimum extrusion temperatures of the ethylene-methacrylic acid copolymer and the cyclic olefin resin can be made closer to each other. Therefore, in this case, a high-quality layer can be formed at high speed.

[0056] Ethylene-methacrylic acid copolymer (EMAA) is, for example, a resin polymerized by a high-pressure method. Commercially available products of ethylene-methacrylic acid copolymer include, for example, "Nucrel (registered trademark) N1108C" manufactured by DuPont-Mitsui Polychemicals Co., Ltd.

[0057] The thickness of the adhesive resin layer 19 is preferably 5 μm or more. The thickness of the adhesive resin layer 19 is preferably in the range of 5 μm to less than 30 μm, and more preferably in the range of 5 μm to 25 μm. If the thickness of the adhesive resin layer 19 is excessively thin, the film formation of the adhesive resin layer 19 becomes unstable. If the thickness of the adhesive resin layer 19 is excessively thick, adsorption is likely to occur.

[0058] The adhesive resin layer 19 may further contain an additive, such as one or more of an antioxidant, an ultraviolet absorbing agent, a light stabilizer, an antistatic agent, an antiblocking agent, a flame retardant, a crosslinking agent, and a colorant.

[0059] (Sealant layer) The sealant layer 20 contains a cyclic olefin resin. The sealant layer 20 imparts heat sealability to the laminate 1, and also plays a role in enhancing the non-adsorption property of the laminate 1.

[0060] The sealant layer 20 may have a single-layer structure or a multi-layer structure. For example, the sealant layer 20 may have a single-layer structure containing a cyclic olefin resin, or a multi-layer structure including a layer containing a cyclic olefin resin and another resin layer. Examples of the other resin layer include polyolefin films such as polyethylene films and polypropylene films.

[0061] The cyclic olefin resin is preferably a ring-opening metathesis polymer (COP) obtained by polymerizing a cyclic olefin by a metathesis ring-opening polymerization reaction, a copolymer of a cyclic olefin and an α-olefin (chain olefin), i.e., a cyclic olefin copolymer (COC), or a mixture thereof.

[0062] As the cyclic olefin, any cyclic hydrocarbon having an ethylenically unsaturated bond and a bicyclo ring can be used. The cyclic olefin is preferably one having a bicyclo[2.2.1]hept-2-ene (norbornene) skeleton.

[0063] As a cyclic olefin resin obtained from a cyclic olefin having a norbornene skeleton, for example, a ring-opening metathesis polymer of a norbornene monomer can be used. As a commercially available product of such a ring-opening metathesis polymer, for example, "ZEONOR (Zeonor; registered trademark)" manufactured by Zeon Corporation, can be mentioned. As a cyclic olefin resin obtained from a cyclic olefin having a norbornene skeleton, for example, a norbornene-based cyclic olefin copolymer can be used. As a commercially available product of such a cyclic olefin copolymer, for example, "Apel (registered trademark)" manufactured by Mitsui Chemicals, Inc. and "TOPAS (registered trademark)" manufactured by TOPAS ADVANCED POLYMERS GmbH and sold by Polyplastics Co., Ltd. can be mentioned.

[0064] As the cyclic olefin resin, for example, a cyclic olefin copolymer, which is a copolymer obtained by copolymerizing ethylene and norbornene using a metallocene catalyst, can be suitably used. A cyclic polyolefin copolymer has the same non-adsorption property as a cyclic olefin polymer, and is inexpensively available. As a copolymer obtained by copolymerizing ethylene and norbornene using a metallocene catalyst, a copolymer containing a repeating unit represented by formula (a) and a repeating unit represented by formula (b) can be used. Such a cyclic olefin resin can be used. An example of a commercially available product of this type is "TOPAS (registered trademark)" manufactured by TOPAS ADVANCED POLYMERS GmbH and sold by Polyplastics Co., Ltd.

[0065] [ka]

[0066] Suitable cyclic olefin resins have a glass transition temperature in the range of, for example, 60°C to 100°C.

[0067] The sealant layer 20 may further include an additive. The additive is, for example, one or more of a lubricant, an antioxidant, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antiblocking agent, a flame retardant, a crosslinking agent, and a colorant. As the lubricant, for example, a higher fatty acid metal salt, an aliphatic alcohol, a polyglycol, a triglyceride, a wax, a phenolic compound, or a mixture containing one or more of them can be suitably used for the purpose of improving processability. The wax is a naturally derived wax, for example, a mineral wax such as montan wax. Alternatively, the wax may be a synthetic wax such as polyethylene wax.

[0068] From the viewpoint of physical strength, the sealant layer 20 is preferably a biaxially stretched film. Another advantage of biaxial stretching is that it is possible to produce a thin film. Since cyclic olefin resins are prone to draw resonance, it is difficult to directly produce a thin film, for example, with a thickness of 30 μm or less, by extrusion.

[0069] The thickness of the sealant layer 20 is preferably 5 μm or more. The thickness of the sealant layer 20 is preferably in the range of 10 μm to 50 μm, and more preferably in the range of 10 μm to 30 μm. If the sealant layer 20 is made excessively thin, the film formation of the sealant layer 20 may become unstable, and the effect of suppressing adsorption may become small. On the other hand, if the sealant layer 20 is made excessively thick, the improvement in the effect of suppressing adsorption with the increase in the thickness of the sealant layer 20 is slight.

[0070] The sealant layer 20 is laminated so as to face the first adhesive layer 18, with a first laminate having a base layer 11, a barrier layer 14, an intermediate base layer 17, and a first adhesive layer 18 in that order, sandwiched between them and an adhesive resin layer 19, which is an extruded resin layer formed by an extrusion lamination method.

[0071] For example, when the sealant layer 20 is a film, the laminate 1 can be formed by sandwiching the adhesive resin layer 19, which is an extruded resin layer, between the first laminate and the sealant layer 20 and laminating them by a sandwich lamination method. Alternatively, the laminate 1 can be formed by laminating the adhesive resin layer 19 and the sealant layer 20 on the first adhesive layer 18 of the first laminate by extrusion lamination or co-extrusion lamination.

[0072] <Modification> Various modifications are possible for the laminate. As described above, the laminate according to the present embodiment may further include an adhesive layer not shown in FIG. 1, and may further include a printing layer not shown in FIG. 1. Modifications will be described below with reference to FIG. 2 and FIG. 3. The matters described with reference to FIG. 1 can be applied to the laminate according to the modification described herein, either alone or in combination.

[0073] FIG. 2 is a partial cross-sectional view that shows a schematic view of a laminate according to one modified example. 2 comprises, in this order, a substrate layer 11, a second adhesive layer 13, a barrier layer 14, a third adhesive layer 15, an intermediate substrate layer 17, a first adhesive layer 18, an adhesive resin layer 19, and a sealant layer 20. Except for the inclusion of the second adhesive layer 13 between the substrate layer 11 and the barrier layer 14, and the inclusion of the third adhesive layer 15 between the barrier layer 14 and the intermediate substrate layer 17, the laminate 2 is similar to the laminate 1 described with reference to FIG.

[0074] The second adhesive layer 13 and the third adhesive layer 15 can be formed, for example, by applying a two-component curing urethane adhesive that is generally used as an adhesive for dry lamination. As a coating method, a known method such as a gravure coating method or a roll coating method can be used.

[0075] The second adhesive layer 13 and the third adhesive layer 15 have a mass per area in a dry state of, for example, 1.25 to 7.5 g / m 2 and in another example, 2.5 to 5.0 g / m 2 is in the range.

[0076] FIG. 3 is a partial cross-sectional view that illustrates a schematic representation of a laminate according to another modified example. 3 includes, in this order, a base material layer 11, a printed layer 12, a second adhesive layer 13, a barrier layer 14, a third adhesive layer 15, a printed layer 16, an intermediate base material layer 17, a first adhesive layer 18, an adhesive resin layer 19, and a sealant layer 20. Except for including the printed layer 12 between the base material layer 11 and the second adhesive layer 13, and including the printed layer 16 between the third adhesive layer 15 and the intermediate base material layer 17, the laminate 3 is similar to the laminate 2 described with reference to FIG. 2.

[0077] The printed layers 15 and 16 are layers formed to put the laminate 3, or a package or packaged article including the laminate 3, into practical use as a commercial product. The printed layers 15 and 16 are layers formed of inks containing additives such as various pigments, extender pigments, plasticizers, desiccants, and stabilizers added to conventionally used ink binder resins such as urethane, acrylic, nitrocellulose, rubber, and vinyl chloride, and display patterns such as characters and designs. The printed layers 15 and 16 can be formed, for example, by known printing methods such as offset printing, gravure printing, and silk screen printing, or known coating methods such as roll coating, knife edge coating, and gravure coating.

[0078] The thickness of the printed layers 15 and 16 is not particularly limited, and in one example is in the range of 0.1 to 5 μm, and in another example is in the range of 0.2 to 1 μm. EXAMPLES

[0079] Tests carried out in relation to the present invention are described below. <1> Laminate manufacturing (Example 1) The laminate 2 shown in FIG. 2 was produced by the following method. First, a biaxially oriented polyethylene terephthalate film (PET) having a thickness of 12 μm was prepared as the base layer 11. Also, an aluminum foil having a thickness of 20 μm was prepared as the barrier layer 14.

[0080] Next, an ester-based urethane adhesive (aromatic two-component curing type) was applied to one main surface of the base layer 11 to form a second adhesive layer 13. The base layer 11 and the barrier layer 14 were laminated by a dry lamination method with the second adhesive layer 13 sandwiched therebetween to form a laminate a consisting of the base layer 11 / second adhesive layer 13 / barrier layer 14. The mass per area (application amount) of the second adhesive layer 13 in a dry state was 3.0 g / m 2 It was decided.

[0081] Next, the same adhesive as that used for the second adhesive layer 13 was applied to the barrier layer 14 side of the laminate a to form a third adhesive layer 15. The laminate a and the intermediate base material layer 17 were laminated by a dry lamination method with this third adhesive layer 15 sandwiched therebetween to form a laminate b consisting of the base material layer 11 / second adhesive layer 13 / barrier layer 14 / third adhesive layer 15 / intermediate base material layer 17. The application amount (in a dry state) of the third adhesive layer 15 was 3.0 g / m 2 As the intermediate base material layer 17, a biaxially oriented nylon film (ONY) having a thickness of 15 μm was used.

[0082] Next, a biuret-type aliphatic one-component curing adhesive of diisocyanate monomer was applied to the intermediate substrate layer 17 side of the laminate b to form a first adhesive layer 18, thereby producing a first laminate consisting of substrate layer 11 / second adhesive layer 13 / barrier layer 14 / third adhesive layer 15 / intermediate substrate layer 17 / first adhesive layer 18. Here, a biuret-type hexamethylene diisocyanate (mixture mass ratio: hexamethylene diisocyanate / ethyl acetate=5 / 95, solid content concentration: 4.98 mass%) was used as the biuret-type aliphatic one-component curing adhesive of diisocyanate monomer. The coating amount (dry state) of the first adhesive layer 18 was 0.25 g / m 2 It was decided.

[0083] Next, an adhesive resin layer 19 was formed by extrusion lamination on the first adhesive layer 18 side of the first laminate, and the first adhesive layer 18 and the sealant layer 20 were attached so as to face each other with the adhesive resin layer 19 sandwiched therebetween, thereby producing the laminate 2 shown in FIG. 2. Here, as the adhesive resin layer 19, low-density polyethylene resin (LDPE) (L417, manufactured by Sumitomo Chemical Co., Ltd.; MFR 5 g / 10 min, density 0.922 g / cm 3 The adhesive resin layer 19 had a thickness (thickness after lamination) of 13 μm. As the sealant layer 20, a biaxially stretched film of cyclic olefin copolymer (COC) (TSC-1, manufactured by Kurabo Industries, Ltd.; thickness 25 μm) was used.

[0084] (Example 2) The coating amount (dry state) of the first adhesive layer 18 is 0.25 g / m 2 From 0.15 g / m 2 Laminate 2 was produced in the same manner as in Example 1, except for the above changes.

[0085] (Example 3) The coating amount (dry state) of the first adhesive layer 18 is 0.25 g / m 2 from 0.05 g / m 2 Laminate 2 was produced in the same manner as in Example 1, except for the above changes.

[0086] (Example 4) Laminate 2 was produced in the same manner as in Example 1, except that the sealant layer 20 was changed from a biaxially oriented film of cyclic olefin copolymer (COC) to an unoriented film of cyclic olefin copolymer (COC) (ME-1, manufactured by Kuraray Industries, Inc.; thickness 25 μm).

[0087] (Example 5) A laminate 2 was produced in the same manner as in Example 1, except that the adhesive resin layer 19 was changed from low-density polyethylene resin (LDPE) to ethylene-methacrylic acid copolymer (EMAA) (N1108C, manufactured by Dow Mitsui Polychemicals Co., Ltd.).

[0088] (Example 6) Laminate 2 was produced in the same manner as in Example 1, except that the barrier layer 14 was changed from aluminum foil to an alumina-deposited PET film (GL-ARH, manufactured by Toppan Printing Co., Ltd.; thickness 20 μm).

[0089] (Example 7) Laminate 2 was produced in the same manner as in Example 1, except that the sealant layer 20 was changed from a biaxially oriented film of cyclic olefin copolymer (COC) to a coextruded two-layer film of cyclic olefin copolymer (COC) / polyethylene (MP series M3400MP, manufactured by DIC Corporation; thickness 30 μm).

[0090] Comparative Example 1 A laminate was produced in the same manner as in Example 1, except for the following points. That is, the adhesive A was applied to the intermediate base material layer 17 side of the laminate b consisting of the base material layer 11 / second adhesive layer 13 / barrier layer 14 / third adhesive layer 15 / intermediate base material layer 17 obtained in Example 1 to form an adhesive layer. The sealant layer 15 was laminated on this adhesive layer by dry lamination to obtain a laminate consisting of the base material layer 11 / second adhesive layer 13 / barrier layer 14 / third adhesive layer 15 / intermediate base material layer 17 / adhesive layer / sealant layer 20. Here, the adhesive A was an ester-based urethane adhesive (aromatic two-component curing type) that was the same as the adhesive used in the second adhesive layer 13 and the third adhesive layer 15. As the sealant layer 20, the same biaxially stretched COC film as the film used in Example 1 was used.

[0091] Comparative Example 2 A laminate was produced in the same manner as in Comparative Example 1, except that adhesive A was changed from an ester-based urethane adhesive (aromatic two-component curing type) to an ester-based urethane adhesive (aliphatic two-component curing type).

[0092] Comparative Example 3 A laminate was produced in the same manner as in Example 1, except that the sealant layer 20 was changed from a biaxially oriented film of cyclic olefin copolymer (COC) to a linear low-density polyethylene film (LLDPE) (MZ434, manufactured by Tamapoly Co., Ltd.; thickness 25 μm).

[0093] Comparative Example 4 A laminate was produced in the same manner as in Example 1, except that the sealant layer 20 was changed from a biaxially stretched film of cyclic olefin copolymer (COC) to an ethylene-methacrylic acid ionomer film (EMAA) (N1108C manufactured by Dow Mitsui Polychemicals Co., Ltd.; thickness 25 μm).

[0094] Comparative Example 5 A laminate was manufactured in the same manner as in Example 1, except that the sealant layer 20 was changed from a biaxially oriented film of cyclic olefin copolymer (COC) to unoriented polypropylene (CPP) (RS-503C, manufactured by Idemitsu Unitech Co., Ltd.; thickness 25 μm).

[0095] Comparative Example 6 A laminate was produced in the same manner as in Example 1, except that the intermediate substrate layer 17 was changed from the biaxially oriented nylon film (ONY) to a polyethylene terephthalate (PET) film having a thickness of 12 μm.

[0096] Comparative Example 7 A laminate was produced in the same manner as in Example 1, except that the barrier layer 14 was changed from aluminum foil to polyethylene terephthalate (PET).

[0097] <2> evaluation Evaluation samples were prepared using each of the laminates of Examples 1 to 7 and Comparative Examples 1 to 7. First, two test pieces measuring 10 cm x 10 cm were cut out from each laminate, and the two test pieces were stacked so that the sealant layer was on the inside, and three sides were heat-sealed to form a bag shape. Next, menthol was placed in the bag, and the remaining side was heat-sealed to prepare a menthol-containing packaging bag as an evaluation sample. These samples were stored for one month in a thermostatic chamber at a temperature of 40°C and a relative humidity of 75%, and then the adsorption resistance, lamination strength, and water vapor barrier property were evaluated by the methods described below.

[0098] (Menthol adsorption resistance) After removing the pharmaceutical ingredient menthol from each sample, the packaging bag was cut into small pieces. The cut test pieces were immersed in methanol to obtain a menthol extract. The menthol extract was then analyzed by high performance liquid chromatography to quantify the amount of menthol adsorbed to the packaging bag. Based on this, the amount of menthol adsorbed per area of ​​the packaging bag was calculated. The amount of menthol adsorbed was 3.0 μg / cm 2 The pass criteria is 3.0μg / cm 2 Below A, 3.0μg / cm 2 The results were summarized in Table 1.

[0099] (Laminate strength) After removing the pharmaceutical ingredient menthol from each sample, the packaging bag was cut into 15mm-wide strips, and the barrier layer and the sealant layer were peeled off at a tensile speed of 300mm / min using an RTF-1250 manufactured by A&D Co., Ltd., to measure the laminate strength. A laminate strength of 15.0N / 15mm or more was set as the pass standard, with 15.0N / 15mm or more being rated as A and less than 15.0N / 15mm being rated as B. The results are summarized in Table 1.

[0100] (Water vapor permeability) After removing the pharmaceutical ingredient menthol from each sample, the packaging bag was cut into an octagonal shape using a special tool, and measurements were performed for 3 cycles of 20 minutes each under an atmosphere of temperature (40)°C and relative humidity (90)% using a water vapor transmission rate measuring device (MOCON, Hitachi High-Tech Science Corporation), and the average value was taken as the water vapor transmission rate. 2 / day or less is the pass standard, and 1.0g / m 2 / day or less is A, 1.0g / m 2 / day or more was rated as B. The results are summarized in Table 1.

[0101] [Table 1] The results shown in Table 1 demonstrate that the laminate of this embodiment, as a packaging laminate, is excellent in all respects, including adsorption resistance to components contained in the contents, peel resistance to highly permeable substances, and water vapor barrier properties.

[0102] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]

[0103] 1, 2, 3...laminate, 11...base material layer, 12...printed layer, 13...second adhesive layer, 14...barrier layer, 15...third adhesive layer, 16...printed layer, 17...intermediate base material layer, 18...first adhesive layer, 19...adhesive resin layer, 20...sealant layer.

Claims

1. A laminate comprising, in this order, a base material layer, a barrier layer, an intermediate base material layer, a first adhesive layer, an adhesive resin layer, and a sealant layer, wherein the intermediate base material layer contains a polyamide-based resin, the first adhesive layer contains an isocyanate compound having two or more isocyanate groups, the adhesive resin layer contains a low-density polyethylene resin or an ethylene-methacrylic acid copolymer, and the sealant layer contains a cyclic olefin-based resin.

2. The first adhesive layer has a mass per area of ​​0.05 to 0.25 g / m 2 The laminate according to claim 1, wherein the thickness of the laminate is in the range of 100 nm to 150 nm.

3. 3. The laminate according to claim 1, wherein the sealant layer is a biaxially oriented film.

4. The laminate according to claim 1 , wherein the barrier layer comprises an aluminum foil or an inorganic oxide layer.

5. forming a first laminate comprising, in order, the substrate layer, the barrier layer, the intermediate substrate layer, and the first adhesive layer; and The adhesive resin layer is extruded, and the first laminate and the sealant layer are laminated together so that the first adhesive layer and the sealant layer face each other with the adhesive resin layer sandwiched therebetween; or laminating the adhesive resin layer and the sealant layer on the first adhesive layer side of the first laminate by extrusion molding or co-extrusion molding; A method for producing the laminate according to claim 1 , comprising:

6. A package comprising the laminate according to any one of claims 1 to 4.

7. A packaged article comprising the package according to claim 6 and contents packaged therein.

Citation Information

Patent Citations

  • Laminated packaging material

    JP1994055714A

  • Package material and paper container made of the same

    JP2013249069A

  • Packaging material

    JP2015030113A

  • Packaging material and paper container comprising the same

    JP2016020095A

  • Laminate and its manufacturing method

    JP4306278B2